Metode Tutor Sebaya dalam Pembelajaran Ansambel Musik Rekorder - Riza Rosadi (Program Studi Pendidikan Seni Pertunjukan FKIP ULM, 2016)
AbstractThis experimental research aims to determine the learning outcomes of musical ensembles, recorder (soprano) in SMP Negeri 2 Banjarmasin using two methods of learning: peer tutoring and conventional. This study also seek out differences in the results of the two methods. Two classes of samples in this study were taken by purposive random sampling technique. Peer tutoring learning methods applied in the experimental class, and conventional teaching methods applied in the control class. Data collection techniques used are tests and documentation, while data analysis using descriptive statistical techniques. The results of this study indicate that: (1) the learning outcomes of students who use peer tutoring learning methods that are in a good qualifying with an average value of 82.91; (2) the results of student learning using the conventional method is more than enough in qualifying with an average value of 78.90; and; (3) test based on statistics found differences in student learning outcomes were significant between experimental class using peer tutors to grade control using conventional methods. Similarly it can be said that results for students in the experimental class is better than learning outcomes in the control class.Keywords: peer tutoring, learning, music ensembles, recorder